Pengembangan Pemasaran Makanan Khas Palito Daun Sebagai Produk Unggulan Daerah Kampar di Desa Naumbai, Kecamatan Kampar, Kabupaten Kampar, Provinsi Riau - HB, Gusliana; Andrikasmi, Sukamarriko; Ardiayanto, Syaifullah Yophi; Habibie, Dedi Kusuma; Yunus, Wan Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Naumbai Village is a village located in Kampar District, Kampar Regency, Riau Province. Naumbai Village was formed and designated as a preparatory village in 2003. The people of Naumbai Village come from the indigenous Malay tribe, the majority of whom work as farmers. With 1,017 women, Naumbai village is well known for its residents' skills in making various kinds of traditional foods such as galopuong, bomban leaf lopek, sarikayo, and leaf palito. Palito daun is very well known and famous among the people of Kampar, because several years ago it was used as a traditional food icon by the Kampar regional government on the anniversary of the district which is known as the veranda of the Mecca of Riau. A business marketing development strategy can be the key to success or even failure in a company. Determining the right target and which business development strategy should be used to achieve business goals can be a risky decision. When a business has a strong strategy, aligned with business goals, and implemented well, the strategy has the potential to increase growth and high profitability.